Interaction between Parsley Petroselinum Crispum and Cadmium: Field Study on Some Agricultural Areas in Baghdad City and Experimental Study on Albino Mice Males - A. Yousuf, Huda; Shnawa Al-Zubaidi, Fawzi; H. Yousif, Waleed (Iraqi Journal of Science, 2023)
This study consists of two parts, field and experimental. In field part; cadmium concentrations were measured in soil and parsley Petroselinum crispum samples of five different agricultural areas in Baghdad city. These areas were located in Al-Rashdiah, Tounis quarter, Al-Shamasiah quarter, Al-Itaifiah and Al-Twaithah. Soil cadmium concentrations were (1.72, 1.25, 1.52, 3.45 and 3.33) mg/kg in Al- Rashdiya, Tunis quarter, Al- Shamasiya quarter, Al- Attaifiya and Al-Tuaithah respectively, while concentrations in parsley were (0.28, 0.26, 0.28, 0.39 and 0.38) mg/kg respectively. Experimentally, five groups of albino mice males (10 mice each) were administered with different concentrations of cadmium (0.0, 0.25, 0.5, 0.75 and 7.5) mg Cd/kg b.w. orally by using gavages needle for 60 days according to 5 days/week protocol, another five mice groups were administered with the same concentrations of cadmium mentioned above and 0.1 ml of parsley Petroselinum crispum juice. At the end of the experiment, mice liver and kidney were isolated to measure the bioaccumulation of cadmium.